The Role of Sharia Microfinance Institutions in Fulfilling the Capital Needs of Micro, Small and Medium Enterprises: Case Study of BPRS AL WASLIYAH MEDAN - Aura sabbrina; Anisya Putri Ertani Daulay; Shara Jumiati Siregar; Irfan Andinata; fitri hayati (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This research aims to analyze the role of sharia microfinance institutions, with a focus on PT. BPRS Al-Washliyah, in providing capital financing for MSME players, as well as identifying factors that influence the effectiveness of sharia financing in supporting the development of small businesses. One of the main challenges faced is the lack of understanding by MSME actors regarding the principles of sharia finance, thus hampering the use of these services. This research uses a qualitative descriptive approach through interviews, observations and documentation analysis to explore the relationship between sharia microfinance institutions and the growth of MSMEs, as well as finding solutions to the obstacles faced. The research results show that the Murabahah financing scheme implemented by PT. BPRS Al-Washliyah is in accordance with sharia principles as regulated in DSN Fatwa Number 04/DSN-MUI/IV/2000. This financing provides easy capital with a ceiling of up to 50 million rupiah, which contributes to the business development of MSME players. However, collateral requirements remain a challenge for some customers. To overcome these obstacles, banks implement strategies such as in-depth credit analysis, regular monitoring, and competitive product promotions. These steps demonstrate the bank's commitment to supporting the growth of MSMEs, strengthening the local economy, and encouraging sharia-based financial inclusion in society.